Perceptions of HPV vaccination and pharmacist-physician collaboration models to improve HPV vaccination rates - Benjamin S. Teeter (Elsevier, 2021)
Background: Human Papillomavirus (HPV) is the most common sexually transmitted disease in the United States (US), with 12 cancer causing strains. Vaccination rates in the southern US fall below the national average. Pharmacists provide an opportunity to improve vaccination rates. Objectives: The objectives of this study were to 1) identify barriers and facilitators to providing the HPV vaccine and Vaccines for Children (VFC) program participation in pharmacies and clinics, and 2) assess pharmacy staff, clinic staff, and parent perceptions of 3 collaboration models to improve HPV vaccination. Methods: A developmental formative evaluation was conducted with pharmacy staff, primary care clinic staff, and parents of adolescent children. Interview guides were informed by the Consolidated Framework for Implementation Research (CFIR). Barriers and facilitators to HPV vaccination and VFC participation were explored. Additionally, acceptability of 3 collaboration models were explored: 1) a shared-responsibility model in which a physician provides the first dose of HPV vaccine with the second provided in the pharmacy, 2) a pharmacy-based model in which a clinic refers patients to the pharmacy to receive both doses, and 3) an insourced model in which pharmacists schedule days to provide the vaccine in the collaborating clinic. Results: Twenty-nine interviews were conducted between August 2019 and June 2020. Both pharmacy and clinic staff had positive views toward the HPV vaccine and vaccinations in general. Pharmacists and physicians reported parental awareness and education as a barrier to HPV vaccination. Counseling about HPV vaccine was reported as being more time-consuming because of the stigma associated with the vaccine. Parents were willing to have their children vaccinated for HPV in the pharmacy but desired their child's physician be involved in the immunization process. The shared-responsibility model was the most favored of the 3 collaboration models. Conclusion: Perceptions of the HPV vaccine and vaccination in pharmacies were positive. Collaboration between clinics and pharmacies to improve HPV vaccination rates is viewed positively by pharmacy staff, clinic staff, and parents. This study will guide implementation of pharmacist-physician collaborative models to improve vaccination through pharmacy participation in the VFC program and HPV vaccination.